The role of pharmacists in developing countries: the current scenario in Pakistan - Masood Imran; Ahmad Maqsood; Ibrahim Mohamed; Hassali Mohamed; Azhar Saira; Shafie Asrul (BMC, 2009)
Abstract During the past few years, the pharmacy profession has expanded significantly in terms of professional services delivery and now has been recognized as an important profession in the multidisciplinary provision of health care. In contrast to the situation in developed countries, pharmacists in developing countries are still underutilized and their role as health care professionals is not deemed important by either the community or other health care providers. The aim of this paper is to highlight the role of pharmacists in developing countries, particularly in Pakistan. The paper draws on the literature related to the socioeconomic and health status of Pakistan's population, along with background on the pharmacy profession in the country in the context of the current directions of health care. The paper highlights the current scenario and portrays the pharmacy profession in Pakistan. It concludes that although the pharmacy profession in Pakistan is continuously evolving, the health care system of Pakistan has yet to recognize the pharmacist's role. This lack of recognition is due to the limited interaction of pharmacists with the public. Pharmacists in Pakistan are concerned about their present professional role in the health care system. The main problem they are facing is the shortage of pharmacists in pharmacies. Moreover, their services are focused towards management more than towards customers. For these reasons, the pharmacist's role as a health care professional is not familiar to the public.